(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2001)
By evaluating the strong and the weak points o f the Latgale region we can assert that its power lies in its natural resources which are luxurious in their mild modesty, with the best-preserved environmental originality in the north-eastern part o f Eutrope. The weak point of Latgale is the poverty of the population and disarrayed infrastructure. To eliminate the weakness, balanced education o f the population is needed, as well as profitable farming projects and support investments. A co-operation project was worked out by the Latvian Council o f Science “Optimisation o f the economic and social development of Latgale During four years “Foundations o f farming in Latgale ” have been developed. This report deals with what has been done; in monographs, available just here, the members of the conference can obtain detailed information.